Gêneros discursivos argumentativos nos anos finais do Ensino Fundamental: uma proposta de sequência didática - Nadiane Batista de Souza (2024)
ABSTRACT This study investigated Portuguese language teaching in the final years of elementary school, focusing on argumentative discursive genres. Based on theorists such as Bakhtin, Bronckart and Marcuschi, as well as the National Curricular Parameters and the National Common Curricular Base, the work reflected on the process of argumentative construction in opinion articles produced by students in the 8th year of Elementary School, through analysis theoretical, elaboration and application of a didactic sequence that aimed to expand students' ability to position themselves in the face of controversial topics and argue about them in a persuasive way. Using a qualitative approach, we carried out class observations and field diary records, focusing specifically on the 8th year of the Antônio de Souza Lobo Sobrinho Municipal School. The objective was to identify the main difficulties faced by students in textual production, especially in opinion articles. Through the study I concluded that it is essential to review the approach to teaching Portuguese, integrating knowledge and skills to develop students' argumentative competence. The adoption of teaching sequences focused on these genres can remedy gaps in learning, promoting more coherent, critical and effective writing, fundamental both for academic success and for the exercise of active citizenship. Keywords: Portuguese Language. argumentative discursive genres, argumentativeness, didactic sequences